INFORMATION AND ANALYTICAL SUPPORT FOR BUSINESS VALUATION - HLUSHKO, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the theoretical foundations of information and analytical support for business valuation. A thorough scientific analysis of the category of “information and analytical support” as a component of the valuation process that integrates the functions of collection, systematization, verification of reliability, analytical processing, and use of information is conducted. It has been established that the quality, completeness, timeliness, and relevance of the information base significantly affect the reliability and validity of business valuation results, especially in conditions of a highly dynamic economic environment, information asymmetry, and limited access to statistical and financial data during martial law. The types of information used in the valuation process are systematized according to the following criteria: source of origin (internal/external), functional purpose (planning, accounting, regulatory and reference, operational), and time aspect (retrospective, current, forecast). Particular attention is paid to sources of information that can be applied in practice in conditions of limited availability of official data.The author proposes a structural-logical model of information and analytical support for business valuation, which reflects the sequence of stages of information formation and processing, the logic of interrelations between key elements of the valuation process, and the integration of the results obtained into effective management decisions. The developed model is universal in nature and can be adapted to the operating conditions of enterprises in various industries, particularly in environments of high uncertainty. It can be legitimately considered as a conceptual basis for improving valuation practices and increasing their analytical effectiveness. Prospects for further research are related to deepening the scientific and methodological foundations of business valuation, taking into account digital transformations and the challenges of wartime.
Keywords: business value; business valuation; information and analytical support; value-oriented management; information